LITERATUR RIVIEW : TELAAH PENGOBATAN MODERN DAN TRADISONAL PADA PENYAKIT ASAM URAT (GOUT) - Siska Ratna Dewi; Eko Sri Wahyuningsih; Neni Sri Gunarti (Jurnal Buana Farma, 2023)
Metabolic disorders are disorders that increase uric acid levels (hyperurasemia). This disease is often found both in Indonesia and other countries on the Asian continent. Xantahuine Oxidase Inhibitor class drugs such as allopurinol and febuxostat are recommended as the first line of treatment, but it should be noted that continuous use of Xantahunine Oxidase Inhibitors can cause side effects of toxicity in the digestive system and increase acute attacks of gout at the start of therapy. Therefore, many studies involving many herbal plants are expected to have antihyperuricemia activity because herbal plants have a lower risk of toxicity and side effects. Based on research that has been carried out, Red Ginger (Zingiber officinale var. Amarum), Bay Leaves (Syzygium polyanthum), Seruhan Herb (Peperomia pellucida (L.) Kunth, Meniran (Phyllanthus niruri Linn.), Bamboo Shoot Extract (Schizostachyum brachycladum Kurz), Wood Secang (Caesalpinia sappan L.), Tangkur Fern (Polypodium feei), White Dragon (Hylocereus undatus), Malu Princess Plant (Mimosa pudica L.), Soursop Leaves (Annona muricata L.), Sparattosperma Leucanthum, Mahkota Dewa (Phaleria macrocarpa ( Scheff.) Boerl.), Mangosteen Fruit Peel (Garcinia mangostana L.), Dioscorea tokoro Makino, Chatupatika have antihyperuricemia activity. Therefore, in this review the antihyperuricemia activity of fifteen of these plants will be discussed. The results obtained from several articles are Some of these plants have antihyperuricemia properties through xanthine oxidase inhibition tests and reduce uric acid levels in test animals, so they have the potential to be developed as drugs for hyperuricemia